Bazi Bushen capsule attenuates cognitive deficits by inhibiting microglia activation and cellular senescence. (31st December 2022) - Ji, Chuanyuan; Wei, Cong; Li, Mengnan; Shen, Shuang; Zhang, Shixiong; Hou, Yunlong; Wu, Yiling
Abstract: Context: Bazi Bushen capsule (BZBS) has anti-ageing properties and is effective in enhancing memory. Objective: To find evidence supporting the mechanisms and biomarkers by which BZBS functions. Materials and methods: Male C57BL/6J mice were randomly divided into five groups: normal, ageing, β-nicotinamide mononucleotide capsule (NMN), BZBS low-dose (LD-BZ) and BZBS high-dose (HD-BZ). The last four groups were subcutaneously injected with d -galactose (d -gal, 100 mg/kg/d) to induce the ageing process. At the same time, the LD-BZ, HD-BZ and NMN groups were intragastrically injected with BZBS (1 and 2 g/kg/d) and NMN (100 mg/kg/d) for treatment, respectively. After 60 days, the changes in overall ageing status, brain neuron morphology, expression of p16 INK4a, proliferating cell nuclear antigen (PCNA), ionized calcium-binding adapter molecule 1 (Iba1), postsynaptic density protein 95 (PSD95), CD11b, Arg1, CD206, Trem2, Ym1 and Fizz1, and the senescence-associated secretory phenotype (SASP) factors were observed. Results: Compared with the mice in the ageing group, the HD-BZ mice exhibited obvious improvements in strength, endurance, motor coordination, cognitive function and neuron injury. The results showed a decrease in p16 INK4a, Iba1 and the upregulation of PCNA, PSD95 among brain proteins. The brain mRNA exhibited downregulation of Iba1 ( p < 0.001), CD11b ( p < 0.001), and upregulation of Arg1 ( p < 0.01), CD206 ( p < 0.05), Trem2 ( p < 0.001), Ym1 ( p < 0.01), Fizz1 ( p < 0.05) and PSD95 ( p < 0.01), as well as improvement of SASP factors. Conclusions: BZBS improves cognitive deficits via inhibition of cellular senescence and microglia activation. This study provides experimental evidence for the wide application of BZBS in clinical practice for cognitive deficits.